EVALUASI PASCA PENDIDIKAN PELATIHAN KEPEMIMPINAN TINGKAT III TERHADAP KINERJA APARATUR DKI JAKARTA - Farihah Sulasiah; Sarah Hidayati (LP3M Universitas Muhammadiyah Muara Bungo, 2021)
In order to carry out bureaucratic reform and the effectiveness of public services, a strategy is needed that is capable of forming superior civil servants, competitive, and capable of becoming leaders of change. Implementation of Level III Leadership Education and Training within the DKI Jakarta Provincial Government is one of the competency development efforts for echelon III officials in order to achieve job competency requirements. In addition, this training is also intended to form administrator officials capable of leading the implementation of all public service activities as well as government administration and development in their respective agencies. This study aims to provide an overview of the performance of the personnel after attending the PIM Tk. III of 2019 within the DKI Jakarta Provincial Government.The method used is descriptive quantitative with primary data sources derived from surveys using a 360-degree performance appraisal questionnaire to alumni respondents participating in PIM Tk Education and Training. III, alumni co-workers, direct superiors and personnel. The results of data analysis show that the Level III Leadership Training in DKI Jakarta Province in 2019 has a positive impact on alumni performance as shown by the assessment of saffing respondents, co-workers, and superiors on each performance variable.